2010
DOI: 10.1001/dmp.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Individual Disaster Recovery: A Socioecological Framework

Abstract: ABSTRACTBackground: Disaster recovery is a complex phenomenon. Too often, recovery is measured in singular fashion, such as quantifying rebuilt infrastructure or lifelines, without taking in to account the affected population's individual and community recovery. A comprehensive framework is needed that encompasses a much broader and far-reaching construct with multiple underlying dimensions and numerous causal pathways; without the consideration of a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 19 publications
5
57
0
Order By: Relevance
“…Holistic, interdisciplinary torture rehabilitation models emerged early on (by 1984) in Copenhagen by RCT group (e.g., Ortmann, Genefke, Jakobson, & Lunde, 1987). Variants and expansions of the model have been emerged and further developed, for example, the wraparound approach for psycho-social rehabilitation of torture survivors (e.g., Silove, Tarn, Bowles, & Reid, 1991;Kira, 2002Kira, , 2010, ecological group therapy models that focus on community healing (Kira, Ahmed et al, 2012b), post-disaster ecological recovery model, (Abramson et al, 2010). While such models have social and ecological validity as inherent programmatic feature, empirical evidence of its effectiveness is not yet established through controlled double blind studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holistic, interdisciplinary torture rehabilitation models emerged early on (by 1984) in Copenhagen by RCT group (e.g., Ortmann, Genefke, Jakobson, & Lunde, 1987). Variants and expansions of the model have been emerged and further developed, for example, the wraparound approach for psycho-social rehabilitation of torture survivors (e.g., Silove, Tarn, Bowles, & Reid, 1991;Kira, 2002Kira, , 2010, ecological group therapy models that focus on community healing (Kira, Ahmed et al, 2012b), post-disaster ecological recovery model, (Abramson et al, 2010). While such models have social and ecological validity as inherent programmatic feature, empirical evidence of its effectiveness is not yet established through controlled double blind studies.…”
Section: Discussionmentioning
confidence: 99%
“…While such models have social and ecological validity as inherent programmatic feature, empirical evidence of its effectiveness is not yet established through controlled double blind studies. However, there is strong empirical evidence for the effectiveness of some of their variants (e.g., Abramson et al, 2010). There is some empirical evidence of the effectiveness of multi-component multi-systemic wraparound torture rehabilitation approach (e.g., McColl et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A bias analysis conducted by the G-CAFH Study team demonstrated that there are no significant differences due to attrition between the cohort at wave one and at wave four. Additional information on study design and methodology has been published elsewhere [38,39]. …”
Section: Methodsmentioning
confidence: 99%
“…In the past decade, there have been efforts to design a systematic model to explain and measure the recovery process after disasters [14,19]. The scarcity of measurable indicators and the focus of studies on case studies have limited the possibility to compare the outcomes between different incidents and their follow up [14,19,20]. For this purpose, in various studies, efforts have been made to identify and examine the components and dimensions of life recovery after disasters and to design indicators for measuring the outcomes.…”
Section: Indicators Of Recoverymentioning
confidence: 99%
“…Abramson study (2010) was conducted to develop an operational measure of individual recovery and determined, and a stable housing, economic stability, physical health, mental health, and social role adaptation have been considered as important factors [20]. In addition, Dwyer study (2014) considered structural and non-structural recovery at community level.…”
Section: Indicators Of Recoverymentioning
confidence: 99%